2011
DOI: 10.1017/s0022149x11000125
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of pouched amphistome parasites (Trematoda: Gastrothylacidae) using ribosomal ITS2 sequence and secondary structures

Abstract: Members of the family Gastrothylacidae (Trematoda: Digenea: Paramphistomata) are parasitic in ruminants throughout Africa and Asia. In north-east India, five species of pouched amphistomes, namely Fischoederius cobboldi, F. elongatus, Gastrothylax crumenifer, Carmyerius spatiosus and Velasquezotrema tripurensis, belonging to this family have been reported so far. In the present study, the molecular phylogeny of these five gastrothylacid species is derived using the second internal transcribed spacer (ITS2) seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…In recent years, several molecular tools including sequence data related to conserved domains have unveiled their utility in molecular identification, taxonomy, systematics and phylogeny of floral, faunal and microbial species, too (Huang et al 2006;Prasad et al 2009a, b;Wiemers et al 2009;Yao et al 2010;Sharma et al 2012). Since Woese and Fox (1977), the nuclear ribosomal repeat cistrons have also been widely implied for parasites (Littlewood and Olson 2001;Waeschenbach et al 2007;Jyrwa et al 2009;Goswami et al 2009;Tandon et al 2010;Prasad et al 2011;Ghatani et al 2012). Molecular phylogeny has advanced our understanding of comparative studies in basic and applied biology and more generally of their position within the phylum Platyhelminthes (Brooks and Hoberg 2001;Tandon et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several molecular tools including sequence data related to conserved domains have unveiled their utility in molecular identification, taxonomy, systematics and phylogeny of floral, faunal and microbial species, too (Huang et al 2006;Prasad et al 2009a, b;Wiemers et al 2009;Yao et al 2010;Sharma et al 2012). Since Woese and Fox (1977), the nuclear ribosomal repeat cistrons have also been widely implied for parasites (Littlewood and Olson 2001;Waeschenbach et al 2007;Jyrwa et al 2009;Goswami et al 2009;Tandon et al 2010;Prasad et al 2011;Ghatani et al 2012). Molecular phylogeny has advanced our understanding of comparative studies in basic and applied biology and more generally of their position within the phylum Platyhelminthes (Brooks and Hoberg 2001;Tandon et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Miura et al (2005) reported the absence of heterozygosity in ITS-1 genes, which did not provide any support of gene fl ow among different lineages. Some workers suggested the ITS-2 as effective marker for species identifi cation, phylogenetic relations and developmental stages as well as molecular epidemiology and infection control (Rinaldi et al, 2005;Curran et al, 2006;Bazsalovicsová et al, 2010;Lotfy et al, 2010;Shylla et al, 2011;Ghatani et al, 2012;Phalee et al, 2014;Bian et al, 2013;Portier et al, 2012). In helminth parasites, ITS pseudogenes and mitochondrial genes are present and identifi cation of ITS region is not easy due to non-protein coding nature as compared to mitochondrial genes (Benasson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Ghatani et al (2012) established the molecular phylogeny of fi ve gastrothylacid species using ITS-2 and secondary structure predictions. Inter-specifi c variations were noticed among the fi ve species through sequencing results, whereas secondary structures analyses expressed structural similarities.…”
Section: Gastrothylacidae (Stiles and Goldberger 1910)mentioning
confidence: 99%
“…The identical nature of the ITS2 secondary structure can be attributed to similarity in rRNA biogenesis among eukaryotes; its folding pattern plays an important role in processing of mature rRNA (Joseph et al, 1999) and structures are maintained during evolution through transitions/transversions, although mutations occur frequently (Coleman, 2007;Keller et al, 2010). The utility of ITS2 secondary structure for characterizing parasites has also been demonstrated (Shylla et al, 2011;Ghatani et al, 2012). A high degree of similarity in the ITS2 secondary structures of Posthodiplostomum sp.…”
Section: Discussionmentioning
confidence: 99%